Telemedicine and Mobile Health Technology Are Effective in the Management of Digestive Diseases: A Systematic Review - Helsel, Brian C.; Williams, Joel E.; Lawson, Kristen; Liang, Jessica; Markowitz, Jonathan (Digestive diseases and sciences, 2018)
Background Mobile applications and interactive websites are an increasingly used method of telemedicine, but their use lacks evidence in digestive diseases. Aim This study aims to explore digestive disease studies that use telemedicine to effectively manage disease activity, help monitor symptoms, improve compliance to the treatment protocol, increase patient satisfaction, and enhance the patient-to-provider communication. Methods EBSCO, PubMed, and Web of Science databases were searched using Medical Subject Headings and other keywords to identify studies that utilized telemedicine in patients with digestive disease. The PRISMA guidelines were used to identify 20 research articles that had data aligning with 4 common overlapping themes including, patient compliance (n = 13), patient satisfaction (n = 11), disease activity (n = 15), and quality of life (n = 13). The studies focused on digestive diseases including inflammatory bowel disease (n = 7), ulcerative colitis (n = 4), Crohn’s Disease (n = 1), irritable bowel syndrome (n = 6), and colorectal cancer (n = 2). Results From the studies included in this systematic review, patient compliance and patient satisfaction ranged between 25.7–100% and 74–100%, respectively. Disease activity, measured by symptom severity scales and physiological biomarkers, showed improvements following telemedicine interventions in several, but not all, studies. Similar to disease activity, general and disease-specific quality of life showed improvements following telemedicine interventions in as little as 12 weeks in some studies. Conclusion Telemedicine and mobile health technology may be effective in managing disease activity and improving quality of life in digestive diseases. Future studies should explore both gastrointestinal and gastroesophageal diseases using these types of interventions.